Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1080/07366290701512725
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Caprolactam with an Alternative Benign Solvent in a Pulsed Disc and Doughnut Column

Abstract: Caprolactam is obtained by extraction using organic solvents like benzene, toluene, or chlorinated hydrocarbons. As an alternative solvent, the mixed solvent heptane-heptanol (40 mass %) was selected in previous studies based on a relatively high distribution ratio of caprolactam, a low mutual solvent solubility, beneficial physical properties, and a low distribution ratio of impurities. Now, the hydraulic and mass transfer characteristics of the extraction of caprolactam in a pulsed disc and doughnut column (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Since no published correlations are available for prediction of mass transfer coefficient in pulsed disc and doughnut columns, the Kumar and Hartland correlations are commonly used for description of the mass transfer performance in pulsed disc and doughnut columns (Van Delden et al, 2006;Grinbaum, 2006). In the present work, the possibility of using these correlations for prediction of the overall mass transfer coefficient is examined.…”
Section: Prediction Of the Continuous Phase Overall Mass Transfer Coementioning
confidence: 99%
See 1 more Smart Citation
“…Since no published correlations are available for prediction of mass transfer coefficient in pulsed disc and doughnut columns, the Kumar and Hartland correlations are commonly used for description of the mass transfer performance in pulsed disc and doughnut columns (Van Delden et al, 2006;Grinbaum, 2006). In the present work, the possibility of using these correlations for prediction of the overall mass transfer coefficient is examined.…”
Section: Prediction Of the Continuous Phase Overall Mass Transfer Coementioning
confidence: 99%
“…The comparison of experimental results with those calculated by the Kumar and Hartland correlations is shown in Figure 5. Van Delden et al (2006) also used these correlations for description of mass transfer performance of extraction of caprolactam with toluene in a pulsed disc and doughnut column. Vol.…”
Section: Prediction Of the Continuous Phase Overall Mass Transfer Coementioning
confidence: 99%
“…Among the various types of extraction columns, the pulsed disc and doughnut extraction column is one type of extractor whose application has rarely been referred to the literature [13][14][15][16]. An installation of the pulsed disc and doughnut columns to treat the uranium solutions from Western Mining Corporations in South Australia has shown that these columns have a clear advantage over the mixer-settlers.…”
Section: Introductionmentioning
confidence: 97%
“…[8] The axial dispersion and backflow model are most appropriate for describing axial mixing and mass transfer for column scale-up designs, [9] and have been applied to the PDDC. [10][11][12][13][14][15] The most widely used model, the ADM, was proposed by Danckwerts, and is an intuitive and simple solution. [5] In this model, mass transfer factors are considered in terms of the number of mass transfer units (N oc ), whereas all nonideal factors are considered in terms of a single parameter, namely the axial dispersion coefficient, which is consistent with Fick's law with a clear physical meaning.…”
Section: Introductionmentioning
confidence: 99%